Substituição parcial da farinha de peixe por diferentes hidrolisados proteicos na dieta de Penaeus vannamei (BOONE, 1934) em diferentes fases de crescimento - Negrini, Celma (2024)
The objective of the present work was to evaluate the effects of including different protein hydrolysates as partial replacements for fishmeal in the diets of post-larvae and juveniles of Pacific white shrimp (P. vannamei) on zootechnical performance, proximate chemical composition, digestive enzyme activity and total hemocyte count.In both phases, 24 experimental units were used in a recirculation system with clear water. The experimental design was completely randomized, with six treatments, namely: Control (fish meal); Hydrolyzed chicken protein (PHF); Enzymatic hydrolyzate of chicken feathers; Aquabite®; PHF + maltodextrin; and PHF + yeast; and four repetitions each.In the nursery phase, 30 shrimp were housed with an average weight of 0.2 g per experimental unit, fed for 28 days with the experimental diets. In the fattening phase, five shrimp with an average weight of 1.35 g per experimental unit were stored and fed for 50 days. At the end of both experimental phases, all shrimp were counted, weighed and measured to determine survival, biomass gain, apparent feed conversion and specific growth rate. The total length of the antenna was also measured. The chemical composition of the body and feed, the enzymatic activities of the hepatopancreas and the total count of hemocytes in the hemolymph were analyzed.The data obtained were submitted to ANOVA and the Tukey test. In the nursery phase, there was no statistical difference between treatments in any of the analyzed parameters (p<0.05), indicating that all protein hydrolysates evaluated can be used as partial replacements for fishmeal in rations, maintaining equivalent and adequate digestive enzyme activities, health, growth and body composition of shrimp. During the fattening phase, there were no significant differences between the treatments in the zootechnical performance parameters and in the total hemocyte count of the shrimp (p<0.05). Regarding well-being, the shrimp's antenna length had higher values in treatments with Enzymatic hydrolyzate of chicken feathers,PHF + maltodextrin and PHF + yeast (p>0.05), and its integrity is a sign that the animal was in good conditions of well-being in the environment of production.In body chemical composition based on natural matter, the parameters of dry matter, ether extract and mineral residue were affected by the treatments (p<0.05). Regarding the analysis of digestive enzymes, there was an influence of treatments on the enzymes amylase and trypsin (p<0.05). P. vannamei in the fattening phase had the ability to modulate the activities of the digestive enzymes amylase and trypsin depending on the ingredient used, ensuring availability of nutrients for cell metabolism. The results from both production phases showed that all protein hydrolysates evaluated can be included (6%) as partial replacements for fishmeal in P. vannamei rations during the nursery and fattening phases, maintaining good shrimp performance.